Total Synthesis of a 6, 6‐Spiroketal Metabolite, Dinemasone A. Issue 3 (27th November 2012) - Raji Reddy, Chada; Srikanth, Boinapally; Dilipkumar, Uredi; Rao, Kakita Veera Mohana; Jagadeesh, Bharatam
Abstract: The stereoselective total synthesis of dinemasone A has been accomplished. The key reactions, Sharpless asymmetric epoxidation, lithium‐mediated epoxy alcohol opening, and double‐intramolecular hetero‐Michael addition, gave access to dinemasone A from lactic acid esters. The stereochemistry at the spiro carbon was determined using extensive NMR studies. Abstract : The stereoselective total synthesis of dinemasone A was accomplished in a longest linear sequence of 14 steps using double‐intramolecular hetero‐Michael addition as the key spiroketalisation reaction.